تطبيق مبادئ جودة الخدمات في المؤسسات التعليمية - راضية اللبي; سجية سوداني; سعاد صوفية (university of eloued جامعة الوادي, 2024)
"تحاول هذه الدراسة الإجابة والبحث عن مدى تطبيق مبادئ جودة الخدمات في المؤسسات التعليمية، حيث تطرقنا إلى كل مبدأ من مبادئ الجودة ومن ثمّ محاولة اختبار تطبيق هذه المبادئ على مدرستين تعليميتين ذات طابع خاص؛ومن أجل تحقيق أهداف الدراسة تم اختيار المنهج الوصفي التحليلي حيث استخدمنا أداة الاستبانة التي احتوت على 62 فقرة طبّقت على عيّنة عشوائيّة مكوّنة من 44 أستاذا وإداريا، وتم التّأكّد والتّحقّق من ثباتها باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS 22 لتحليل النّتائج. ومن أهم ما توصلت إليه الدراسة هو أن كلا من مبدأ التركيز على المستفيد والقيادة وكذا مبدأ العمل الجماعي والتحسين المستمر، وأيضا مبدأ اتخاذ القرار بناء على الأدلة؛ ومبدأ إدارة العلاقات تطبقهم المؤسسة بمستويات متفاوتة وبشكل عال، بناء على اختبار تطبيق عبارات الاستبانة؛ ما يدلل على أن المؤسستين تلتزمان بتطبيق مبادئ جودة الخدمات وبعض أبعاد جودة الخدمات التعليمية. " "This study attempts to answer the following question: To what extent are the principles of service This study attempts to answer the following question: To what extent are the principles of quality services applied in educational institutions? We touched on identifying each of the principles of quality and then activating them in two schools of a special nature. In order to achieve the objectives of the study، the descriptive analytical approach was chosen in a questionnaire. It consists of 62 items and was applied to a random sample of 44 professors and administrators، and its stability was confirmed and verified using the Statistical Package for the Social Sciences (SPSS 22) program to analyze the results. The study reached the following results: The principle of focusing administrative functions in the institution، the principle of leadership، the principle of teamwork، in addition to the availability of a communications network and the principle of continuous improvement، and also the principle of decision-making based on evidence and the principle of relationship management are applied by the institution at very high levels، and therefore it is committed to Applying the quality of services at a high level. "
Keywords: مبادئ جودة الخدمات، المؤسسات التعليمية Principles of Quality of Services Educational institutions